2014
DOI: 10.3109/08880018.2014.961214
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of HLA-Haploidentical Hematopoietic Stem Cell Transplantation With Post-Transplantation Cyclophosphamide for Advanced Pediatric Malignancies

Abstract: PTCY is feasible in children; however, for a better outcome in such patients with advanced malignancies, some modifications are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
2
29
2
5
Order By: Relevance
“…A similar concept involves administering cyclophosphamide (50 mg/kg) to patients for 2 days starting 3 days after haplo-HSCT from T-cell replete donors to eliminate alloreactive T cells while sparing nonalloreactive/quiescent donor T cells. [29][30][31][32][33] This selective depletion is simpler than the genetic modification described here, and appears to effectively prevent GVHD. However, because every patient is treated with cyclophosphamide irrespective of GVHD, unnecessary depletion of critical T-cell subsets may occur, potentially delaying immune reconstitution and increasing opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…A similar concept involves administering cyclophosphamide (50 mg/kg) to patients for 2 days starting 3 days after haplo-HSCT from T-cell replete donors to eliminate alloreactive T cells while sparing nonalloreactive/quiescent donor T cells. [29][30][31][32][33] This selective depletion is simpler than the genetic modification described here, and appears to effectively prevent GVHD. However, because every patient is treated with cyclophosphamide irrespective of GVHD, unnecessary depletion of critical T-cell subsets may occur, potentially delaying immune reconstitution and increasing opportunistic infections.…”
Section: Discussionmentioning
confidence: 99%
“…Среди наибо-лее важных -наличие данных, свидетельствующих о модулирующих иммунный ответ с целью профилак-тики оРТПХ свойствах циклофосфана (ЦФ), введен-ного в Д+3, Д+4 в дозе 50 мг/кг веса реципиента после гапло-ТГСК, а также моделирование клеточного соста-ва трансплантата, полученного из костного мозга (КМ), путем изменения направления поляризации от Th1-лим-фоцитов к Th2-лимфоцитам с помощью гранулоцитар-ного колониестимулирующего фактора (Г-КСФ), вводи-мого донору в дозе 5 мкг/кг в течение 3 дней до миелоэксфузии и 4 дней до забора ГСК крови [10][11][12].…”
Section: Introductionunclassified
“…Показано, что при использовании неманипулиро-ванного трансплантата при гапло-ТГСК у детей 5-лет-няя БРВ в 1-й и 2-й ремиссии при остром миелобласт-ном лейкозе (ОМЛ) составляет 82,5 и 59,4 %, остром лимфобластном лейкозе (ОЛЛ) -68,9 и 56,6 % соот-ветственно [11,12], в рецидиве при ОМЛ -42,9 %, при ОЛЛ -22,2 % [11 -13].…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Kanda et al [63,109] prospectively evaluated the safety and efficacy of alemtuzumab in PBSCT from HLA-haploidentical donor with continuous CsA and sMTX. Sawada et al [110] reported the feasibility of HLAhaploidentical BMT and PBSCT with posttransplantation cyclophosphamide for pediatric patients.…”
Section: Gvhd Prophylaxis Regimens For Hla-haploidentical Donor Transmentioning
confidence: 99%